2006
DOI: 10.1074/jbc.m510731200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Role of (Bacterio)chlorophyll Ligated in the Energetically Unfavorable β-Position

Abstract: Chlorophyll is attached to apoprotein in diastereotopically distinct ways, by ␤-and ␣-ligation. Both the ␤-and ␣-ligated chlorophylls of photosystem I are shown to have ample contacts to apoprotein within their proteinaceous binding sites, in particular, at C-13 of the isocyclic ring. The H-bonding patterns for the C-13 1 oxo groups, however, are clearly distinct for the ␤-ligated and ␣-ligated chlorophylls. The ␤-ligated chlorophylls frequently employ their C-13 1 oxo in H-bonds to neighboring helices and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…Intermolecular hydrogen bond between the peripheral C3 acetyl group and neighboring residues modulates the functional properties, especially the excitation energies of BChl in LH complexes (Fowler et al 1994;Sturgis and Robert 1997). Hydrogen bonding between the C13 1 keto carbonyl group of bacteriochlorophyll-B850 of the b-subunit to the hydroxyl group of serine(-4) of the a-subunit significantly contributes to the assembly and stability of LH2 without apparently affecting its spectral properties (Garcia-Martin et al 2006a;Kwa et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Intermolecular hydrogen bond between the peripheral C3 acetyl group and neighboring residues modulates the functional properties, especially the excitation energies of BChl in LH complexes (Fowler et al 1994;Sturgis and Robert 1997). Hydrogen bonding between the C13 1 keto carbonyl group of bacteriochlorophyll-B850 of the b-subunit to the hydroxyl group of serine(-4) of the a-subunit significantly contributes to the assembly and stability of LH2 without apparently affecting its spectral properties (Garcia-Martin et al 2006a;Kwa et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…[1,3,5] Recent findings showed that the 13 1 -carbonyl of β-ligated chlorophylls in LH II has a strong tendency to H-bond with the neighbouring protein subunits, thus manifesting the key role of the ligation face in the antennae structure. [6] 4932 unit forms an ion pair with the chlorin acid group. The binding mechanism was further confirmed by association constants (K a ) obtained from titration experiments in CDCl It is very likely that selective chlorin β-face ligation has been formerly achieved by using a covalent approach by trivially replacing the phytyl group of chlorophyll with an N-propyl imidazole moiety.…”
Section: Introductionmentioning
confidence: 99%
“…Axial ligation to the central magnesium atom has long been recognized as critical for the binding of (B)Chl and thus for the assembly of (B)Chl proteins 6, 7. There are, however, numerous additional possibilities of interactions with the substituents; in particular, H‐bonding to the carbonyl groups seems to be widespread 8, 9. Additionally, there is the stereochemical aspect in (B)Chl ligation 10–12.…”
Section: Introductionmentioning
confidence: 99%
“…The two faces of the chlorin macrocycle are diastereotopic, and an additional chiral center is therefore generated by ligation of the central magnesium from either the top (α‐type) or the bottom face (β‐type) of the macrocycle [Scheme (C)]; these two ligation states should differ in their binding energies 13, 14. In natural (B)Chl proteins, the two types of ligation are unevenly distributed, and α‐type ligation of (B)Chls is predominant 9, 11. β‐Ligated (B)Chl has been proposed to play an important role in (B)Chl protein assembly 9.…”
Section: Introductionmentioning
confidence: 99%